La chair décevante - Bernier, Jovette (Biblio Fides, 2014)
Sur l'écran, sous les feux de la rampe, la souffrance est divine pour la foule. La même souffrance dans la rue et dans les chambres closes, cela s'appelle du déshonneur. [...] Il y a quelque chose de plus fort que le courage, la tendresse, le dévouement, le sacrifice; il y a plus fort que toi, l'Amour, et toi, la Mort ; plus fort que tout, plus fort que vous tous, il y a la Vie.
Keywords: 1900-1999; 1920-1929; 1930-1939; amériques; approches et analyses; arts; canada; cours; discipline; lit3495; maternité; patriarcat; point de vue situé; premier cycle; périodes historiques; québec; ressource en ligne; roman; régions géographiques; sexualité; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto romance series, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires